2015
DOI: 10.1111/eth.12382
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Wing Coloration in Sex Recognition and Competitor Recognition in Rubyspot Damselflies (Hetaerina spp.)

Abstract: The decision rules that animals use for distinguishing between conspecifics of different age and sex classes are relevant for understanding how closely related species interact in sympatry. In rubyspot damselflies (Hetaerina spp.), the red wing coloration of mature males is hypothesized to be a key trait for sex recognition and competitor recognition within species and the proximate trigger for interspecific male-male aggression. We tested this hypothesis by manipulating the wing coloration of tethered conspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…The early‐season phenotype of H. titia more closely resembles sympatric congeners and is remarkably distinct from the late‐season phenotype, leading early researchers to classify light and dark variants of H. titia as separate species (Appendix S1). Previous studies on sympatric Hetaerina species have linked species differences in male wing coloration to interspecific fighting (Anderson & Grether, , ; Drury & Grether, ; Grether et al ., ) and species differences in female wing coloration to reproductive interference (i.e. heterospecific clasping; Drury et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The early‐season phenotype of H. titia more closely resembles sympatric congeners and is remarkably distinct from the late‐season phenotype, leading early researchers to classify light and dark variants of H. titia as separate species (Appendix S1). Previous studies on sympatric Hetaerina species have linked species differences in male wing coloration to interspecific fighting (Anderson & Grether, , ; Drury & Grether, ; Grether et al ., ) and species differences in female wing coloration to reproductive interference (i.e. heterospecific clasping; Drury et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Males have reddish‐brown body coloration and red wing patches (Figure a), while females have greenish‐brown body coloration and amber wing patches (Figure b). Previous research on a similar species, Hetaerina americana, showed that putting artificial red patches on female wings reduced sexual responses and triggered aggressive responses from territorial males (Grether, Drury, Berlin, & Anderson, ), as predicted by the misdirected aggression hypothesis. This might explain the absence of andromorphic females in Hetaerina , but does not help account for the absence of multiple heteromorphs.…”
Section: Introductionmentioning
confidence: 82%
“…The difference in how males responded to females with red and green bands suggests that body coloration plays a role in sex recognition in Hetaerina , as it does in other odonates (reviewed in Xu, Cerreta, Schultz, & Fincke, ), although aggressive responses to red‐banded females were much less consistent and intense than responses to male intruders (Drury et al., ). By contrast, putting red wing patches on female H. americana eliminated sexual responses and caused the females to be attacked almost as aggressively as male intruders (Grether et al., ). In combination, these studies indicate that any fitness benefits of andromorphic coloration through reduced male mating harassment would likely be offset by costs of misdirected aggression in Hetaerina .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, fine‐scale patterns may play a key role (Grether et al . ). For example, the spot on the caudal peduncle that differentiates C. ocellicaudus from C. melannotus (Fig.…”
Section: Discussionmentioning
confidence: 97%